1999
DOI: 10.1095/biolreprod60.4.914
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of Changes in the Human Corpus Luteum Microvasculature during the Menstrual Cycle1

Abstract: Endothelial cells are the most abundant cell type in the corpus luteum (CL), and changes in blood vessels have been proposed to play a pivotal role in CL regression. We have studied quantitatively the changes in the human granulosa-luteal microvasculature in CL of various ages: young (Days 17-19 of the cycle), mature (Days 20-24), old (Days 25-27), early regressing (follicular phase of the following cycle), and late regressing (luteal phase of the following cycle). Blood vessels were identified by immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 22 publications
3
32
1
7
Order By: Relevance
“…The presence of a dense capillary network by the mid-luteal phase is required for optimal delivery of progesterone precursors to, and progesterone from, the luteal cells, at a time when progesterone concentrations are at a maximum (Al-zi'abi et al, 2002). These findings are in agreement with reports in other species (Niswender et al, 1979;Gaytan et al, 1999;Dickson and Fraser, 2000). In the present study, a decrease in the endothelial cell proliferation during late regression, and at 36 h after PGF 2␣ administration, coincided with an observed decrease in microvessels and progesterone concentrations (Al-zi'abi et al, 2002).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The presence of a dense capillary network by the mid-luteal phase is required for optimal delivery of progesterone precursors to, and progesterone from, the luteal cells, at a time when progesterone concentrations are at a maximum (Al-zi'abi et al, 2002). These findings are in agreement with reports in other species (Niswender et al, 1979;Gaytan et al, 1999;Dickson and Fraser, 2000). In the present study, a decrease in the endothelial cell proliferation during late regression, and at 36 h after PGF 2␣ administration, coincided with an observed decrease in microvessels and progesterone concentrations (Al-zi'abi et al, 2002).…”
Section: Discussionsupporting
confidence: 94%
“…on luteal cells and the remainder of the luteal tissue ×100% (Ferrara et al, 1998;Gaytan et al, 1999). The area of vWF immunostaining was calculated using the Quantimet Image Processing and Analysis System 500 (Leica, Cambridge).…”
Section: Quantification Methodsmentioning
confidence: 99%
“…In the present study, the high number of blood vessels in the late CL, associated with a decrease in vascular areas, might be explained by a decrease in blood vessel lumen and by vessel contraction giving the appearance of concentric rings [36]. This decrease in capillary diameter may lead to a fall in blood flow and could initiate and/or accelerate CL regression [38]. The further fall in blood vessel density and number observed in the mare's CA, might be ascribed to the occlusion of blood vessels that disappear as the residual luteal structure organizes into the corpus albicans [36].…”
Section: Discussionmentioning
confidence: 75%
“…In the ovaries of SAMR mice, strong expressions of eNOS at estrus stage (C lane 2) and of iNOS at estrus and metestrus stages (E lanes 2 and 3) were detected. f u n ct i on o f th e l u te a l c el l s, p ro g es t er o n e p r o d uc t i o n , i s a c c o m p a n ie d b y e x te n s i v e development of the vascular system in LBs [21] and by maximal dilatation of LB capillary vessels [22]. It has been reported that dilatation of the vascular bed in LBs of rat ovaries is mediated by NO, and that the expression of eNOS mRNA in luteal cells, indicating NO production, is related to a decrease in progesterone synthesis [22].…”
Section: Discussionmentioning
confidence: 98%